Gender mainstreaming in housing policies: the pioneer case of the Region of Valencia - Inés Novella Abril; Inés Novella Abril (Frontiers in Sustainable Cities)
This article discusses the implementation of gender mainstreaming in public housing policies in the Region of Valencia, Spain. As a relatively advanced case of gender mainstreaming, the text illustrates the complexity of the processes, some possible stages to take into account, and the diversity of initiatives and actions that can be implemented. The Valencian case is of particular interest because it exemplifies a comprehensive approach to gender mainstreaming in housing policies, which facilitated the development of initiatives aimed at addressing both socioeconomic and spatial gender-based inequalities. The article demonstrates the advantages of combining political determination, favorable regulatory frameworks, and the help of expert knowledge, as evidenced by the experience of collaborations between the Generalitat Valenciana and the UNESCO Chair on Gender of the Universidad Politécnica de Madrid. The process of gender mainstreaming of housing policies in the Valencian region has had a significant impact on various regulations, including the mandatory technical standards on residential building design. This exceptional and relatively pioneering step is developed in the article, which also includes a description of a pilot building that shows the results of integrating gender criteria for the design of residential buildings. The aforementioned case study illuminates the vulnerability inherent in gender mainstreaming initiatives within public policy, emphasizing the necessity of meticulous progression toward the realization of gender equality.